(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The study assessed information and post-harvest food safety handling practices among pumpkin farmers in Ikwo Local Government Area, Ebonyi State. The specific objectives of the study were to: assess post-harvest food safety handling practices, identify the sources of information on post-harvest food safety handling practice and identify the constraints faced by small-holder pumpkin farmers in post-harvest food safety handling practices. Multi-stage sampling procedure was employed for the selection of the respondents while a well-structured questionnaire was used to collect data. Frequency, percentage, mean and factor analysis were used for data analysis with the help of SPSS. The study found that 59.7% of pumpkin farmers were females, the mean age was approximately 47 years, 41.7% obtained primary education, 59.9% were members of social organizations. Furthermore, the study found that 68.75% of the post-harvest food safety handling practices of the respondents were incorrect. Fellow farmers, television and friends/neighbours were among credible sources of information used by the respondents. Volume/income/sensitization, weak institution/prices/ health officers/knowledge were among constraints hindering post-harvest food safety handling. Relevant authorities should ensure that pumpkin farmers have access to training and adequate supports on post-harvest food safety handling practices to prevent contamination of pumpkin products that will promote public health.